The Impact of the Use of Information Technology in Improving the Quality of Services: A Field Study of Fast-Food Restaurants in Jordan - Malkawi, Ahmad Fawwaz (European Scientific Journal, ESJ, 2017)
The study aimed to determine the impact of information technology in improving the quality of the service of fast-food restaurants in Jordan. In achieving the objectives and testing of the hypotheses of this study, a questionnaire was developed especially for the collection of data from a study sample. The number of questionnaires analyzed was 66. By using appropriate statistical tests, the results of the study showed that fast-food restaurants uses information technology to improve the quality of their service. There is a strong relationship between information technology and improving the quality of the service. Also, information technology directly and positively affects the process of improving the quality of service in fastfood restaurants. The study recommended the need to employ information technology more in improving the quality of the service in fast-food restaurants. It also works to achieve greater interaction between information technology and the beneficiaries of the services provided by these restaurants. In addition, there is the need for better use of information technology to form a link between the administration and clients.